KONSELING BERBASIS BUDAYA: KONSELING DI TENGAH KEBERAGAMAN BUDAYA DI INDONESIA - Maqomam Mahmuda; Silvianetri Silvianetri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
The purpose of this article is to examine the existing guidance and counseling programs in Indonesia that focus on cultural values to help students who are not from a cultural tribe and who have a strong cultural tribe, which will be explained in the discussion in the adjustment process. In order to produce a new theory that can be considered rationally, this article analyzes various interesting studies from the perspective of various tribes and cultures. The library research method and literature study are used in this article. According to this analysis, guidance and counseling services are very important to help the learning and adjustment process of students in preventing several obstacles. Usually counseling always involves clients from various cultural backgrounds, so it is very possible that cultural bias will be found between counselors and clients. To avoid this, culture-based counseling is one way to present counselors who can understand and adjust the cultural habits of clients and their environment in the guidance and counseling process.